MOUTHWASH OF Amaranthus hybridus L. LEAF EXTRACT WITH ETHYL ACETATE AS A Streptococcus mutans ANTIBACTERIAL - Yelfi Yelfi; Hadi Susilo; Nia Marlina Kurnia (Universitas Islam Bandung, 2022)
Caries and dental plaque are oral and dental problems. Green spinach (Amaranthus hybridus L.) can be used as medicine and has antibacterial activity. It also benefits human health and is a nutrition source. The phytochemical results of the leaf extract showed that A. hybridus L. contains alkaloids, flavonoids, steroids, saponins, and tannins. This study aimed to determine the inhibitory action of A. hybridus L. leaf extract against the growth of Streptococcus mutans and to formulate A. hybridus L. leaf extract in a mouthwash. The disk diffusion method and brain heart infusion agar medium were used in this study, with five treatment groups: extract concentrations of 25%, 50%, and 100%, positive and negative control were studied. Physical tests, including organoleptic, pH, and viscosity tests, were performed. The pH of A. hybridus L. leaf extract in the mouthwash was 4.80, with a viscosity of 1.2456–1.378 cP. The inhibition zones of antibacterial activity against S. mutans in the extract concentrations of 25%, 50%, and 100% were 1.13, 1.73, and 2.90 mm, respectively. The ethyl acetate extract of A. hybridus L. leaves in mouthwash displayed antibacterial activity against S. mutans, with an average inhibition zone of 0.57 mm. The mouthwash formulation produced an inhibition zone with an average F1 of 0.57 mm and F2 of 1.67 mm.